TIMP3 gene polymorphisms and relation to Ankylosing spondylitis susceptibility in Chinese Han population. (9th August 2019) - Wu, Jiamin; Xiong, Zichao; Sun, Yao; Song, Jiangjiang; Niu, Fanglin; Yan, Mengdan; Jin, Tianbo
Abstract: Background: Ankylosing spondylitis (AS) is a type of chronic progressive inflammatory disease, which often causes significant damage to the patients on the physical function, labour ability and quality of life. The study found that the enzyme system tissue inhibitor of matrix metalloproteinases ( TIMPs ) was important for the development of AS. The aim of this study was to investigate the association of polymorphisms of TIMP3 gene with AS in Chinese Han population. Methods: To evaluate the correlation of TIMP3 polymorphisms with AS risk, Agena MassARRAY was used to determine the genotypes of 268 AS patients and 654 controls. The correlation between TIMP3 variants and AS risk was examined by unconditional logistic regression analysis. Haplotype construction and analysis in TIMP3 were also applied to detect the potential association. Results: We identified that rs11547635 in the TIMP3 gene (odds ratio[OR] = 0.79, 95% confidence intervals [CI]: 0.63–0.98, p = .029) was significantly associated with a decreased risk of AS in the alleles model. Rs715572 AG genotype (OR = 1.57, 95% CI: 1.05–2.34, p = .041) was potentially associated with an increased risk of AS, and also rs715572 in the dominant model (OR = 1.61, 95% CI: 1.10–2.36, p = .013) and log‐additive model (OR = 1.41, 95% CI: 1.07–1.86, p = .016) adjusted by age and gender were significantly correlated with an increased AS risk. Conclusion: These findings suggested that polymorphisms of the TIMP3 gene may be associated with susceptibility to AS.